Equitable Representation of Pregnant and Lactating Women in Clinical Research: A Historical Review and Critical Analysis of Proposed Legislation - Woods, Richard H. (American Journal of Perinatology, 2024)
A long history of policymaking and regulation constructed for the purpose of ensuring adequate fetal and infant protections has inadvertently sanctioned the widespread exclusion of pregnant and lactating patients from biomedical research, leaving a paucity of high quality data necessary for clinical decision-making. Although well-intended, the regulatory classification of pregnant women as “vulnerable,” in conjunction with burdensome enrollment criteria and other factors weighing against broad inclusion, have ultimately placed the health and safety of these women and their babies in jeopardy. Robust measures are urgently needed to overcome patient and physician reluctance, address substantial evidence gaps, and rectify long-standing disparities which precipitate disproportionately poor health outcomes among this population. In February 2023, the Advancing Safe Medications for Moms and Babies Act of 2023 (the Act) was introduced in the United States House of Representatives with the overarching goal of enabling pregnant and lactating women to achieve equitable participation in clinical research and contribute to developing important biomedical knowledge to guide and improve health care delivered to these patients. This review discusses the historical influence of federal human subject protection regulations on the health and clinical treatment of pregnant and lactating women, outlines and critically analyzes the provisions incorporated into the Act, and reflects on the potential long-term impact the Act would have should it be successful in becoming law.Key Points
Keywords: pregnancy; lactation; health policy; health equity; drug safety; clinical research; legislation